PENGARUH POLA ASUH ORANG TUA TERHADAP PENGAMALAN KARAKTER BERTANGGUNG JAWAB REMAJA DI KAMPUNG BUKIT AGUNG KECAMATAN KERINCI KANAN KABUPATEN SIAK - Juwita Turnip; Gimin Gimin; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the presence of teenagers whose lifestyles are not appropriately done by a teenager who visits from parenting parents, consisting of authoritarian, democratic, and Permissive. Formulation of the problem in this research is: